Dynamic control of directional asymmetry observed in ultrafast laser direct writing - Salter, P; Booth, M (2012)
A liquid crystal spatial light modulator (SLM) is used to control the focal symmetry and the associated directional quill effect encountered when using a femtosecond laser for direct laser writing of fused silica. Applying a blazed grating to the SLM effectively introduces pulse front tilt to the fabrication beam and a spatiotemporal asymmetry at the focus. As a result different fabricated features are generated when moving the substrate in opposite directions relative to the tilt. It is additionally shown that inhomogeneous pupil illumination can cause similar directionality in the fabrication via a spatial asymmetry in the focus. © 2012 American Institute of Physics.